Analyzing the Heterogeneous Nature of Inmate Behavior: Trajectories of Prison Misconduct. (September 2017) - Cihan, Abdullah; Davidson, Megan; Sorensen, Jonathan
Researchers have long been interested in stability and changes in offending patterns between and within individuals during the life-course. Using data from the Oregon Department of Corrections and the Oregon State Police, the current study explores misconduct trajectories and also attempts to determine whether certain preprison inmate characteristics specified in the importation model are associated with various misconduct trajectories. Results indicate that there are subgroups of inmates engaged in different patterns of institutional misconduct during the course of years of imprisonment. In addition, certain inmate characteristics can be used to explain the identified heterogeneity in inmate misconduct. Findings from trajectory analyses can be useful to prison officials and policy makers when planning prison services, assistance, and programming for subgroups of inmates.